EFEKTIVITAS PENGGUNAAN DANA DESA UNTUK PEM-BANGUNAN DAN PEMBERDAYAAN MASYARAKAT DI DESA TANDUN BARAT KABUPATEN ROKAN HULU TAHUN 2022 - Raihan, Mukodaf; Marta, Auradian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Village funds are funds sourced from the APBN which are transferred through the Regency/City APBD which are prioritized to finance government administration. These large funds require that their management must be carried out well and accountably. So the research focuses more on applying the principle of effectiveness in the use of Village Funds with the aim of describing the effectiveness of the use of village funds. This research was carried out in West Tandun Village, Tandun District, Rokan Hulu Regency. West Tandun Village is a village located in Tandun District, Rokan Hulu Regency. This research aims to determine the effectiveness of using village funds for development and community empowerment and also the inhibiting factors in their management. This research uses prosperity theory regarding the effectiveness of institutional supervisory policies. This research uses a qualitative method with a descriptive approach. The research location is in West Tandun Village, Tandun District, Rokan Hulu Regency. Data collection techniques were carried out through in-depth interviews, field observations, and documentation studies, using data analysis, namely data reduction, data presentation, and drawing con-clusions. The results of this research explain the effectiveness of the use of village funds used by the West Tandun Village Government for community development and empowerment in four ways, including; Accuracy in determining time, accuracy in calculating costs, accuracy in determining goals, accuracy in targets. The performance of the West Tandun Village Government in 2022 is quite good in terms of using village funds for development, while the use of village funds for empowerment is still not optimal. This is because Human Resources (HR) are not yet fully capable of managing village funds each year, and the facilities and infrastructure owned are still not optimal for managing village funds. Keywords: Effectiveness, Village Funds, Development, Empowerment